ERROR ANALYSIS ON THE USE SIMPLE PAST TENSE IN NARRATIVE TEXT - Tri Wahyu Ajeng Kartini (ETNOLINGUAL, 2022)
The purpose of this research is to analyze of student’s errors on the use of past tense in Narrative text based on the problem that students felt confused about using past tense in their writing especially Narrative text. The method of research is qualitative descriptive. The subject of study researcher choose eight grade (2016/2017) in MTs Darussalam, Cepu. The result show that the researcher found four types of errors : omission, addition, misformation, misodering. Then, the researcher found the highest error made by students is misformation with 52% percentages. This problem influenced by student felt confused to understand simple past because they did not know the meaning and differences between regular verb and irregular verb. Therefore, students claimed if they seldom to practice writing paragraph.